Observation of an unusual mid-stratospheric aerosol layer in the Arctic: possible sources and implications for polar vortex dynamics - M. Gerding; G. Baumgarten; U. Blum; J. P. Thayer; K.-H. Fricke; R. Neuber; J. Fiedler (Annales Geophysicae, 2003)
By the beginning of winter 2000/2001, a mysterious stratospheric aerosol layer had been detected by four different Arctic lidar stations. The aerosol layer was observed first on 16 November 2000, at an altitude of about 38 km near Søndre Strømfjord, Greenland (67° N, 51° W) and on 19 November 2000, near Andenes, Norway (69° N, 16° E). Subsequently, in early December 2000, the aerosol layer was observed near Kiruna, Sweden (68° N, 21° E) and Ny-Ålesund, Spitsbergen (79° N, 12° E). No mid-latitude lidar station observed the presence of aerosols in this altitude region. The layer persisted throughout the winter 2000/2001, at least up to 12 February 2001. In November 2000, the backscatter ratio at a wavelength of 532 nm was up to 1.1, with a FWHM of about 2.5 km. By early February 2001, the layer had sedimented from an altitude of 38 km to about 26 km. Measurements at several wavelengths by the ALOMAR and Koldewey lidars indicate the particle size was between 30 and 50 nm. Depolarisation measurements reveal that the particles in the layer are aspherical, hence solid. In the mid-stratosphere, the ambient atmospheric temperature was too high to support in situ formation or existence of cloud particles consisting of ice or an acid-water solution. Furthermore, in the year 2000 there was no volcanic eruption, which could have injected aerosols into the upper stratosphere. Therefore, other origins of the aerosol, such as meteoroid debris, condensed rocket fuel, or aerosols produced under the influence of charged solar particles, will be discussed in the paper. Trajectory calculations illustrate the path of the aerosol cloud within the polar vortex and are used to link the observations at the different lidar sites. From the descent rate of the layer and particle sedimentation rates, the mean down-ward motion of air within the polar vortex was estimated to be about 124 m/d between 35 and 30 km, with higher values at the edge of the vortex. Key words. Atmospheric composition and structure (aerosols and particles; middle ...